MEMMANG: THE ORAL TRADITION OF LAMPUNG SOCIETY - Karsiwan, Karsiwan; Sari, Lisa Retno (Kementerian Pendidikan dan Kebudayaan, 2021)
The aim of this research was to determine that â€œMemmangâ€ is a part of the oral traditions of Lampung society. The method used in this research was a historical method with data collection techniques through interview, observation, and documentation. The data were analyzed qualitatively. The results showed that (1) Memmang is one of the art of oral traditions of Lampung society, (2) there are three main functions of Memmang as an oral tradition of Lampung society, namely: media of treatment, media for strengthening love matters, and a support activity, both personal and social activities. In the development of the oral tradition of Lampung society, Memmang begun to decline. It was happened because only practiced by a small number of people who lived in the village and still adhered to customary values. Besides, the decline of Memmang was influenced by several aspects, such as (a) the strong belief towards religious values, b) the level of people education has been increased so that society is more rational, (c) the influence of the immigrant society causes the local people be influenced and become more Indonesian, and (d) the decline of values and norms as the result of blended with the values and norms of the immigrant society.Â